Defect-rich rock salt type high-entropy oxide battery material and preparation method and application thereof

By selecting Li and Fe or Li and Mn elements with similar cation radii and significant differences in compound valence in rock salt-type high-entropy oxides, and regulating fuel usage under oxygen-depleted conditions, new rock salt-type high-entropy oxides rich in oxygen vacancies and appropriate lattice distortions, the problem of improving the electrochemical performance of existing rock salt-type high-entropy oxides is solved, and a significant improvement in high-ratio electrochemical energy storage performance has been achieved.

CN119873901AActive Publication Date: 2025-04-25ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510113831.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing rock salt type (Co0.2Cu0.2Mg0.2Ni0.2Zn0.2)O high-entropy oxides are single in chemical composition and cannot further improve the electrochemical performance.

Method used

By selecting Li and Fe elements or Li and Mn elements with similar cation radii and significant differences in compound valence, replace the original metal components, and adjust the amount of fuel, a new type of rock salt-type high-entropy oxide rich in oxygen vacancies and appropriate lattice distortion is quickly prepared under oxygen-depleted conditions.

Benefits of technology

The improvement of high-rate electrochemical energy storage performance was achieved, which was specifically manifested in the charge and discharge cycle test of the electrode material at a current density of 200mA/g. The specific capacity of 350 cycles was 550mAh/g, an increase of 59.9% compared with traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873901A_ABST
    Figure CN119873901A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy materials, and particularly relates to a defect-rich rock salt type high-entropy oxide battery material as well as a preparation method and application thereof. The chemical formula of the material is (LiCoCuMgZnM) O, wherein M is at least one of Mn and Fe. In order to improve the electrochemical performance of the material, the novel rock salt type high-entropy oxide battery material rich in oxygen vacancies and moderate lattice distortion is rapidly prepared under the oxygen-deficient condition through element regulation and control and precise control of the use amount of fuel glycine. Finally, the excellent electrochemical energy storage performance of the electrode material under high magnification is realized. The defect-rich novel rock salt type high-entropy oxide battery material provided by the invention is used as a lithium ion battery negative electrode material, and particularly, the rate capability is remarkably improved. The preparation method of the material is simple and convenient in process, mild in reaction condition and wide in applicability, and can be used for regulating and controlling defects of high-entropy oxides with other crystal structures and chemical components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials, and specifically relates to a defect-rich rock salt type high entropy oxide battery material and a preparation method and application thereof. Background Art

[0002] Rock salt type (Co 0.2 Cu 0.2 Mg 0.2 Ni 0.2 Zn 0.2 )O high entropy oxides have shown great application potential in energy storage, catalysis, and electronic devices due to their unique structural characteristics and excellent performance. Compared with traditional single oxides, the high entropy effect of five or more metal elements gives them excellent structural stability and chemical activity. In the field of catalysis, HEOs are widely used in oxygen reduction, nitrogen reduction, and oxygen evolution reactions through metal synergy effects. In terms of energy storage, HEOs not only have excellent electrical conductivity and thermal stability, but also alleviate the volume expansion problem during battery charging and discharging, and improve capacity and cycle stability. In addition, the abundant oxygen vacancies promote the efficient diffusion of lithium ions and sodium ions. With the deepening of research, this material is expected to play a more important role in the future fields of energy, environmental protection, catalysis, etc.

[0003] In 2015, Rost first used divalent metal oxides (MgO+NiO+CoO with rock salt structure, CuO with black copper structure and ZnO with wurtzite structure) as raw materials and prepared rock salt type (CoO+NiO+CoO) by solid phase sintering method. 0.2 Cu 0.2 Mg 0.2 Ni 0.2 Zn 0.2 )O high entropy oxide. Due to the variable valence state of transition metal cations, currently in addition to (Co 0.2 Cu 0.2 Mg 0.2 Ni 0.2 Zn 0.2 )O, another rock salt type high entropy oxide (LiCoCuMgNiZn)O was also reported (Liu XF, Xing YY, Xu K, et al. Kinetically Accelerated Lithium Storage in High-Entropy (LiMgCoNiCuZn)O Enabled By Oxygen Vacancies. Smal 2022, 18(18): 2200524.). 0.2 Cu 0.2 Mg 0.2 Ni 0.2 Zn0.2 )O to introduce inactive low-valent Li + Or morphology regulation (Liu X, Wang H, Dong L, et al. Molten salt synthesis, morphology modulation, and lithiation mechanism of high entropy oxide for robust lithium storage. Journal of Energy Chemistry 2023, 86: 536-545.) or polyaniline coating (Yen JZ, Yang YC. Tuan HY.. Interface engineering of high entropy Oxide@Polyaniline heterojunction enables highly stable and excellent lithium ion storage performance, Chemical Engineering Journal, 2022, 450: 137924.), has improved its electrochemical performance to a certain extent.

[0004] However, there are currently no reports on optimizing the electrochemical performance of rock-salt oxides by regulating active transition metal elements. Summary of the invention

[0005] The purpose of the present invention is to solve the existing rock salt type (Co 0.2 Cu 0.2 Mg 0.2 Ni 0.2 Zn 0.2 The present invention aims to solve the problem that the chemical composition of high-entropy oxide is single and the electrochemical performance cannot be further improved. The present invention provides a defect-rich rock salt type high-entropy oxide battery material and a preparation method and application thereof. On the one hand, by selecting Li and Fe elements or Li and Mn elements with similar cation radii and significant valence differences to replace the original metal components, a single rock salt type high-entropy oxide is successfully prepared; on the other hand, by adjusting the amount of fuel, a new type of rock salt type high-entropy oxide rich in oxygen vacancies and appropriate lattice distortion is quickly prepared under oxygen-deficient conditions, thereby achieving high-rate electrochemical energy storage.

[0006] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0007] The present invention provides a defect-rich rock salt type high entropy oxide battery material, the chemical formula of which is (LiCoCuMgZnM)O, wherein M is at least one of Mn and Fe.

[0008] The present invention also provides a method for preparing a defect-rich rock salt type high entropy oxide battery material, comprising the following steps:

[0009] 1) weighing a stoichiometric ratio of metal salts according to the chemical formula (LiCoCuMgZnMnM)O, dissolving the metal salts in distilled water, and stirring the mixture to obtain a mixed solution of the metal salts;

[0010] 2) Weighing a certain amount of glycine as a fuel, adding the mixed solution of metal salts obtained in step 1), stirring evenly at room temperature, and placing in an oven to evaporate the water therein to obtain a mixed gel;

[0011] 3) placing the mixed gel obtained in step 2) in a transparent electric furnace and reacting at 850-900° C. for 2-10 minutes to obtain a defect-rich rock salt type high entropy oxide battery material.

[0012] Furthermore, in step 1), the metal salt is a metal nitrate or a mixture of a metal nitrate and a metal chloride.

[0013] Furthermore, in step 2), the temperature of the oven is controlled at 80-100°C.

[0014] Furthermore, in step 2), the molar ratio of the fuel to the total metal cations in the metal salt is 0.4 to 1.1:1.

[0015] The present invention also provides an application of a defect-rich rock salt type high entropy oxide battery material in preparing a negative electrode material for a secondary battery.

[0016] The beneficial effects of the present invention are:

[0017] 1. Through the liquid phase batching method, ensure that the raw materials are evenly mixed at the molecular scale, so that the final product can achieve a precise stoichiometric ratio.

[0018] 2. We selected Li and Fe elements, as well as Li and Mn elements, which have similar cation radii and significant differences in valence, and successfully prepared a new type of rock salt-type high-entropy oxide.

[0019] 3. Glycine is used as fuel, and the amount of fuel is controlled to rapidly react under oxygen-deficient conditions to synthesize rock salt-type high entropy oxides rich in oxygen vacancies and appropriate lattice distortion.

[0020] 4. The defect-rich rock salt-type high entropy oxide designed in the present invention is not only suitable for energy storage, but also has application potential in multiple fields such as catalysis.

[0021] Of course, any product implementing the present invention does not necessarily need to achieve all of the above advantages at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0023] Figure 1 XRD pattern of defect-rich rock salt type (LiCoCuMgZnMn)O high entropy oxide powder prepared in Example 1;

[0024] Figure 2 This is a SEM image of the defect-rich rock salt type (LiCoCuMgZnMn)O high entropy oxide powder prepared in Example 1;

[0025] Figure 3 Schematic diagram of the cycle performance and coulombic efficiency of the defect-rich rock salt type (LiCoCuMgZnMn)O high entropy oxide powder prepared in Example 1;

[0026] Figure 4 This is the XRD pattern of the defect-rich rock salt type (LiCoCuMgZnFe)O high entropy oxide powder prepared in Example 2. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] The present invention uses metal nitrate or part of metal chloride as metal source and glycine as fuel, and synthesizes novel rock salt type high entropy oxide battery materials rich in oxygen vacancies and appropriate lattice distortion by controlling the amount of fuel for rapid reaction under oxygen-deficient conditions.

[0029] The specific embodiments of the present invention are as follows:

[0030] Example 1

[0031] Preparation of rock salt type (LiCoCuMgZnMn)O high entropy oxide:

[0032] According to the chemical formula, the corresponding metal nitrates are weighed in equimolar ratios, specifically: 0.05 mol of LiNO3, Co(NO3)2·6H2O, Cu(NO3)2·3H2O, Mg(NO3)3·6H2O, Zn(NO3)2·6H2O and Mn(NO3)2·4H2O are weighed and dissolved in 20 mL of distilled water, and stirred evenly at room temperature to obtain a mixed solution containing metal nitrates; then 0.17 mol of glycine is added to the above metal salt mixed solution, stirred evenly and then dried at 80°C to obtain a gel; finally, the mixture is reacted in a transparent electric furnace at 900°C for 2 minutes to obtain a new rock salt type (LiCoCuMgZnMn)O high entropy oxide battery active material rich in oxygen vacancies and appropriate lattice distortion.

[0033] The XRD and SEM of the powder material are as follows Figure 1 and Figure 2 As shown. XRD spectrum ( Figure 1 ) shows that the prepared (LiCoCuMgZnMn)O high entropy oxide battery active material has a single rock salt structure and I (111) / I (200) =0.59 (theoretical value is 0.67), which proves that the lattice distortion of the prepared rock salt type high entropy oxide is appropriate. SEM ( Figure 2 ) showed that the prepared high entropy oxide had a porous structure.

[0034] Preparation of working electrode and assembly of lithium-ion battery:

[0035] The samples prepared above were used as active materials, Super P carbon black as conductive agent, and polyvinylidene fluoride (PVDF) as binder, and the mixture was mixed in a mass ratio of 7:2:1, dissolved in N-methylpyrrolidone, and made into slurry. The slurry was then evenly coated on the surface of a clean copper foil, and cut into a working electrode with a diameter of 15.6 mm; finally, a pure lithium sheet was used as the negative electrode, a polypropylene porous membrane was used as the diaphragm, and a solution of 1 mol / L LiPF6 in DMC-EC-DEC (volume ratio 1:1:1) was used as the electrolyte. All operations were performed in a glove box, and finally assembled into a CR2025 button cell.

[0036] The battery charge and discharge experiments were carried out on the Xinwei battery test system and compared with the (Co 0.2 Cu 0.2 Mg 0.2 Ni 0.2 Zn 0.2 )O electrode, the electrochemical performance was compared. Figure 3As shown: the (LiCoCuMgZnMn)O electrode was subjected to charge and discharge cycle tests at a current density of 200 mA / g. Within the voltage range of 0.01 to 3.0 V, the specific capacity was 550 mAh / g after 350 cycles; (Co 0.2 Cu 0.2 Mg 0.2 Ni 0.2 Zn 0.2 )O electrode has a specific capacity of 344 mAh / g under the same test conditions. The results show that the specific capacity is increased by 59.9% under the synergistic effect of element substitution and defects.

[0037] Example 2

[0038] Preparation of rock salt type (LiCoCuMgZnFe)O high entropy oxide:

[0039] According to the chemical formula, the corresponding metal nitrates are weighed in equimolar ratios, specifically: 0.05 mol of LiNO3, Co(NO3)2·6H2O, Cu(NO3)2·3H2O, Mg(NO3)3·6H2O, Zn(NO3)2·6H2O and Fe(NO3)3·9H2O are weighed and dissolved in 20 mL of distilled water, and stirred evenly at room temperature to obtain a mixed solution containing metal nitrates; then 0.17 mol of glycine is added to the above metal salt mixed solution, stirred evenly and then dried at 80°C to obtain a gel; finally, the mixture is reacted in a transparent electric furnace at 900°C for 2 minutes to obtain a new rock salt type (LiCoCuMgZnMn)O high entropy oxide battery active material rich in oxygen vacancies and appropriate lattice distortion.

[0040] The XRD characteristics of the powder material are as follows Figure 4 As shown, the prepared (LiCoCuMgZnFe)O high entropy oxide has a single rock salt structure and I (111) / I (200) =0.55 (theoretical value is 0.67), which proves that the lattice distortion of the prepared rock salt type high entropy oxide is appropriate.

[0041] Example 3

[0042] Preparation of rock salt type (LiCoCuMgZnFe)O high entropy oxide:

[0043] According to the chemical formula, the corresponding metal nitrates are weighed in equimolar ratios, specifically: 0.05 mol of LiNO3, Co(NO3)2·6H2O, Cu(NO3)2·3H2O, Mg(NO3)3·6H2O, Zn(NO3)2·6H2O and Fe(NO3)3·9H2O are weighed and dissolved in 20 mL of distilled water, and stirred evenly at room temperature to obtain a mixed solution containing metal nitrates; then 0.28 mol of glycine is added to the above metal salt mixed solution, stirred evenly and dried at 80°C to obtain a gel; finally, the mixture is reacted in a transparent electric furnace at 900°C for 5 minutes to obtain a new rock salt type (LiCoCuMgZnFe)O high entropy oxide battery active material rich in oxygen vacancies and appropriate lattice distortion.

[0044] The chemical formula of the defect-rich new rock salt type high entropy oxide battery material of the present invention is (LiCoCuMgZnM)O, wherein M is at least one of Mn and Fe. In order to improve the electrochemical performance of the material, the present invention quickly prepares a new rock salt type high entropy oxide battery material rich in oxygen vacancies and moderate lattice distortion under oxygen-deficient conditions by element regulation and precise control of the amount of fuel glycine. Ultimately, the excellent electrochemical energy storage performance of the electrode material at high rate is achieved. A defect-rich new rock salt type high entropy oxide battery material provided by the present invention is used as a negative electrode material for lithium-ion batteries, especially in terms of rate performance. The preparation method of the material has a simple process, mild reaction conditions, and wide applicability, and can be used to regulate high entropy oxide defects of other crystal structures and chemical compositions.

[0045] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A defect-rich rock salt high entropy oxide battery material, characterized in that: The chemical formula of the material is (LiCoCuMgZnM)O, wherein M is at least one of Mn and Fe.

2. The method for preparing a defect-rich rock salt type high entropy oxide battery material according to claim 1, characterized in that: The steps include: 1) weighing a stoichiometric ratio of metal salts according to the chemical formula (LiCoCuMgZnMnM)O, dissolving the metal salts in distilled water, and stirring the mixture to obtain a mixed solution of the metal salts; 2) Weighing a certain amount of glycine as a fuel, adding the mixed solution of metal salts obtained in step 1), stirring evenly at room temperature, and placing in an oven to evaporate the water therein to obtain a mixed gel; 3) placing the mixed gel obtained in step 2) in a transparent electric furnace and reacting at 850-900° C. for 2-10 minutes to obtain a defect-rich rock salt type high entropy oxide battery material.

3. The preparation method according to claim 2, characterized in that: In step 1), the metal salt is a metal nitrate or a mixture of a metal nitrate and a metal chloride.

4. The preparation method according to claim 2, characterized in that: In step 2), the temperature of the oven is controlled at 80-100°C.

5. The preparation method according to claim 2, characterized in that: In step 2), the molar ratio of the fuel to the total metal cations in the metal salt is 0.4 to 1.1:

1.

6. Use of a defect-rich rock salt type high entropy oxide battery material as claimed in claim 1 in preparing a negative electrode material for a secondary battery.

Citation Information

Patent Citations

  • Positive electrode material and electrochemical device comprising same

    CN114762151A

  • High-entropy layered metal oxide, preparation method thereof and sodium ion battery

    CN117832476A

  • High-entropy layered oxide, single-crystal high-entropy positive electrode material and preparation method and application of single-crystal high-entropy positive electrode material

    CN118198347A

  • High-entropy metal oxide material for negative electrode of lithium ion battery as well as preparation method and application of high-entropy metal oxide material

    CN118231640A

  • High-entropy layered oxide having anion / cation covariance, preparation method therefor, and use thereof

    WO2024216766A1